A leitura heideggeriana do livro X das Confissões : memória, vida feliz e tentações - Matias, Juliana Pereira (2014)
Saint Augustine is a philosopher that radiated his thought through the time. His philosophy, no doubt, is a walking to the truth and the one that walks with him will find, in each step, the freedom of man in this truth that perform itself in life. No other work revealed so well this search of Augustine than Confessions. Here a journey begins inside him and in front of men, in a constant praise to God. In this way, here a crossing is opened with the medieval author in this search to this true life, to this beata vita, following the path that leads to the himself of man, arriving the limits of Memory in what he wants to search and find the life of his life. In book X of his Confessions, this walking begins. Heidegger found in Augustine the trajectory to understand the experience of religious life, saw in Saint Augustine a thinker that, even though wrapped in a dogmatic reality, can be interpreted through the eyes of the true Christian life. Heidegger found a life lived always opened and in direction to something determined. Saint Augustine reveals in his Confessions this search that never ends, living in direction to God, being in Him, Living in Him, in a relationship in which life actualize itself. This work will follow the path walked by the young Heidegger to understand in Augustine this search for the himself and for God, exceeding the limits of Memory to, finally, find the happy life, a walk in life itself, in the factual experience of life, in the experience of tentatio that, more than the possibility of lost himself, is too the place where man can find himself.